The etymology of the verbal common in the Semitic languages (the islands) of the Egyptians and the Levant - Zamak, Ali; Al-Shammari, Majeed (Al-Adab Journal, 2025)
Some Egyptian and Levantine researchers worked in etymology of the verbal syllable in Semitic languages (the insular). The aim of this research was to shed light on the opinions that were said about the verbal syllable in the island languages this work revealed the agreemt of the Egyptian and Levantian researchers that the verbal refers to unit of origin. It revealed that the relationship betwe the Semitic (island) language precedes the discovery of the Neskrit language, which was rumored to comparative studies. These studies have prov the existce of a clear relationship betwe the Arabic, Aramaic, Phoician, Hebrew, and other languages through verbal commonality to the mother Semitic (insular) languages.